Assessing and Treating Stereotypical Behaviors in Classrooms Using a Functional Approach. (November 2015) - Bruhn, Allison L.; Balint-Langel, Kinga; Troughton, Leonard; Langan, Sean; Lodge, Kelsey; Kortemeyer, Sara
For years, the assumption has been that stereotypical behaviors functioned only to provide sensory or automatic reinforcement. However, these behaviors also may serve social functions. Given the unsettled debate, functional behavior assessment and functional analysis can be used to identify the exact function of stereotypical behavior and design an intervention matched to that function. In these two studies, we conducted functional behavior assessments on two high school students exhibiting stereotypical behaviors. Although the students' behaviors were topographically and functionally different, function-based interventions appeared effective in reducing these behaviors for both students. Key findings and limitations are discussed for each study, and a general discussion across studies is provided.